Infinite-horizon choice functions - Geir B. Asheim; Walter Bossert; Yves Sprumont; Kotaro Suzumura (University of Oslo, Department of Economics, 2006)
We analyze infinite-horizon choice functions within the setting of a simple linear technology. Time consistency and efficiency are characterized by stationary consumption and inheritance functions, as well as a transversality condition. In addition, we consider the equity axioms Suppes-Sen, Pigou-Dalton, and resource monotonicity. We show that Suppes-Sen and Pigou-Dalton imply that the consumption and inheritance functions are monotone with respect to time—thus justifying sustainability—while resource monotonicity implies that the consumption and inheritance functions are monotone with respect to the resource. Examples illustrate the characterization results.
Keywords: D63; D71; 330; Intergenerational resource allocation; infinite-horizon choice; Soziale Wohlfahrtsfunktion; Intertemporale Allokation; Generationenbeziehungen; Wiederholte Spiele; Theorie